Pengawasan dan Kewenangan Eksekusi Nyata Kasus Perdata - Ilyas, Muhammad (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2023)
This research stems from the many cases of disputes that have been legally binding but the rights have not been fulfilled due to constraints in real execution. A number of cases also require an in-depth understanding of the authority possessed by the Chairman of the District Court. The research method used combines normative and empirical approaches. The research focused on the High Court in the South Sulawesi region. The research subjects included all judges, including the Chief Justice, Registrar, and Substitute Registrar. The results of the study indicate that the implementation of internal supervision of the Chief Justice of the District Court is still ineffective in the implementation of civil case decisions that have permanent legal force. It is necessary to increase effective supervision over the implementation of decisions by the Chief of the District Court and a firm attitude is needed from the High Court and the Supreme Court as higher institutions in stages. In addition, opening up space for justice seekers to consider making extraordinary legal efforts, a better understanding of the types of decisions that can be executed, and solutions to legal obstacles that may arise in the execution process such as the establishment of regulations that can be used as legal instruments for resolving certain relatively complicated decisions, for the sake of justice, expediency and legal certainty in accordance with the value of justice for humanity.